Valuasi Ekonomi Pengembangan Objek Wisata Sumber Daya Pantai Dalam Perspektif Ekonomi Islam (Studi Pada Pantai Kabupaten Lampung Selatan) - Piyo, Piyo Alpinda; Yusuf Bahtiar, Muhammad; Restie Utamie, Zathu (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2024)
Marina Beach, Kedu Beach, and Sanggar Beach, located in Kalianda District, South Lampung Regency, are prime tourist attractions despite challenges like poor road access and scattered waste. This study aims to analyze the influence of income, age, gender, and education level on Willingness to Pay (WTP) and to estimate the economic value of these beaches using the Contingent Valuation Method (CVM). A quantitative approach with mixed methods was applied, with a sample of 100 respondents selected through purposive sampling. Results show that the independent variables significantly influence WTP. The estimated economic value of the three beaches is Rp 673,705,000 per year, with a consumer surplus of Rp 15,600 per visitor. From an Islamic perspective, the beaches meet halal tourism criteria, including good environmental management, prayer facilities, and provision of halal food.